Effectiveness of the sleep apnea-specific hypoxic burden and sleep breathing impairment index in assessing cognitive impairment in children with obstructive sleep apnea - Zhu, Simin; Zhou, Yanuo; Lu, Chendi; Wang, Zitong; Ma, Lina; Niu, Xiaoxin; Xie, Yushan; Xia, Zihan; Su, Yonglong; Yuan, Yuqi; Yang, Jiayi; Lu, Rui; et al. (Frontiers in Pediatrics, 2025)
PurposeThis study investigated cognitive impairment in children with obstructive sleep apnea (OSA) by evaluating the utility of sleep apnea-specific hypoxic burden (SASHB) and sleep breathing impairment index (SBII) compared to the obstructive apnea-hypopnea index (OAHI).MethodsA retrospective analysis included 141 children with suspected OSA from Xi'an Jiaotong University Second Affiliated Hospital (October 2021–October 2024), categorized into OSA (n = 104) and non-OSA (n = 37) groups based on OAHI. Demographic, polysomnography (PSG), and event-related potential (ERP) data were collected. Cognitive function (full, verbal, and performance IQ: FIQ, VIQ, PIQ) was assessed using the China-Wechsler Intelligence Scale (C-WISC). Correlations between cognitive scores, ERP parameters, OAHI, SASHB, and SBII were analyzed.ResultsOSA children exhibited higher rates of snoring/sleep suffocation, prolonged apnea/hypoventilation durations, reduced mean/minimum SaO2, lower REM sleep, and elevated N3 sleep. OAHI and SASHB were higher in the OSA group, but SBII showed no group difference. OSA children had prolonged P300/N100 latencies and lower FIQ, VIQ, and PIQ scores. FIQ inversely correlated with OAHI, SASHB, and SBII; after adjusting for age, sex, and BMI, FIQ remained negatively associated with SBII. SASHB correlated with FIQ only in children <6 years, while OAHI showed no significant correlation. VIQ in younger children negatively correlated with SASHB/SBII, but only with OAHI in older children. PIQ in younger children correlated with OAHI, while no correlations existed in older children. P300 latency positively correlated with OAHI; other ERP parameters showed no associations.ConclusionOSA children demonstrate significant cognitive decline and ERP abnormalities. SASHB and SBII exhibit stronger correlations with cognitive impairment than OAHI, particularly in younger children, highlighting their potential as precise metrics for evaluating cognitive deficits in pediatric OSA.